How elastic a little can be and how much a little can do in Chinese - Zhang, Grace (2016)
© 2016 John Benjamins Publishing Company. Yidian ((Greek passage), a little) in Chinese is commonly considered an indefinite and under-specific quantifier. This study provides some rethinking of yidian through the lens of elasticity theory, based on real-life data from TV discussions. Elasticity theory offers new insights on the study of yidian, arguing that yidian is both an elastic quantifier and a qualifier. The findings show that while yidian indicates a small quantity and lesser degree, it is elastic and functions multi-dimensionally from mitigating to boosting. The frequency distributions of three pragmatic functions (just-right which is unmarked, mitigating and boosting which are marked) suggest that yidian is used more for informational than interpersonal and political purposes. In a positive utterance yidian tends to be a mitigator, but in negation it is a booster. The manifestation of elasticity is in yidian's fluidity, stretchability and strategy, enabling it to stretch to suit various contexts and making it a powerful 'little' word that performs a 'big' role in communication.